Book Review: International Practice Development in Health and Social Care (2nd Edition) - Nicki White (Foundation of Nursing Studies, 2021)
International Practice Development in Health and Social Care (2nd Edition) Editors: Kim Manley, Valerie J. Wilson and Christine Øye Oxford: John Wiley and Sons